Former African Colonies of France in the Focus of Attention of the Great Powers - Harutyunyan, Zhanna (YSU Journal of International Affairs, 2021)
The growing attention of the great powers to the mineral-rich African region with other potentials was the reason why the African continent became a subject of conflict of interest and competition. In this context, in a number of parts of the region, including the former French colonies, there was a struggle between the United States, the USSR, China. Against the background of the political interests of the major international players in Africa France has moved from a unilateral policy to a multilateral one, in which the traces of the creation of the EU are more noticeable․